(untitled) (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: The 2021 European Society of Cardiology Guidelines on valvular heart disease recommend transcatheter aortic valve implantation (TAVI) for patients with symptomatic severe aortic stenosis at low surgical risk and age ≥75 years who are suitable for a transfemoral approach (recommendation class IA) based on two large randomised controlled trials (PARTNER 3 and Evolut Low Risk) comparing transcatheter aortic valve implantation with surgical aortic valve replacement (SAVR). Whether such an approach is cost-effective in Switzerland remains unclear. The aim of this cost-utility analysis was to compare transcatheter aortic valve implantation with SAPIEN 3 versus surgical aortic valve replacement in symptomatic severe aortic stenosis patients at low risk of surgical mortality from the perspective of Swiss compulsory health insurance using data from the PARTNER 3 trial (reflecting specifically the safety and efficacy of the SAPIEN 3 TAVI device). METHODS: A previously published two-stage Markov-based model that captured clinical outcomes from the PARTNER 3 trial was adapted from the perspective of the Swiss compulsory health insurance system, using local or geographically close general population mortality and utility data, unit costs and medical resource use from publicly available sources and based on expert opinion. The model had a lifetime horizon with a 3% yearly discounting factor. The cost–utility analysis estimated changes in both direct healthcare costs and health-related quality-adjusted life years for transcatheter aortic valve implantation compared with surgical aortic valve replacement in patients with symptomatic severe aortic stenosis at low risk of surgical mortality. RESULTS: Overall, transcatheter aortic valve implantation with SAPIEN 3 resulted in lifetime costs per patient of CHF 79,534 and quality-adjusted life years per patient of 9.64, compared with surgical aortic valve replacement lifetime costs and quality-adjusted life years per patient of CHF 76,891 and 8.96, respectively. Compared with surgical aortic valve replacement, transcatheter aortic valve implantation was estimated to offer an incremental improvement of +0.68 quality-adjusted life years per patient at an increased cost of +CHF 2643 per patient over a lifetime horizon. The incremental cost-effectiveness ratio was CHF 3866 per quality-adjusted life year gained and remained below CHF 50,000 per quality-adjusted life year gained across several sensitivity analyses. CONCLUSIONS: This analysis suggests that transcatheter aortic valve implantation using the SAPIEN 3 device is likely to be a highly cost-effective alternative for symptomatic severe aortic stenosis patients at a low risk of surgical mortality, treated in the contemporary Swiss setting. These findings may help to inform a holistic approach when making policy decisions for the management of this patient group.